Allogeneic hematopoietic cell transplantation in patients with chronic phase chronic myeloid leukemia in the era of third generation tyrosine kinase inhibitors: A retrospective study by the chronic malignancies working party of the EBMT. Issue 1 (31st October 2022) - Chalandon, Yves; Sbianchi, Giulia; Gras, Luuk; Koster, Linda; Apperley, Jane; Byrne, Jenny; Salmenniemi, Urpu; Sengeloev, Henrik; Aljurf, Mahmoud; Helbig, Grzegorz; Kinsella, Francesca; Choi, Goda; et al.
Abstract: Following the introduction of tyrosine kinase inhibitors (TKI), the number of patients undergoing allogeneic hematopoietic cell transplantation (allo‐HCT) for chronic phase (CP) chronic myeloid leukemia (CML) has dramatically decreased. Imatinib was the first TKI introduced to the clinical arena, predominantly utilized in the first line setting. In cases of insufficient response, resistance, or intolerance, CML patients can subsequently be treated with either a second or third generation TKI. Between 2006 and 2016, we analyzed the impact of the use of 1, 2, or 3 TKI prior to allo‐HCT for CP CML in 904 patients. A total of 323‐, 371‐, and 210 patients had 1, 2, or 3 TKI prior to transplant, respectively; imatinib ( n  = 778), dasatinib ( n  = 508), nilotinib ( n  = 353), bosutinib ( n  = 12), and ponatinib ( n  = 44). The majority had imatinib as first TKI ( n  = 747, 96%). Transplants were performed in CP1, n  = 549, CP2, n  = 306, and CP3, n  = 49. With a median follow‐up of 52 months, 5‐year OS for the entire population was 64.4% (95% CI 60.9–67.9%), PFS 50% (95% CI 46.3–53.7%), RI 28.7% (95% CI 25.4–32.0%), and NRM 21.3% (95% CI 18.3–24.2%). No difference in OS, PFS, RI, or NRM was evident related to the number of TKI prior to allo‐HCT or to the type of TKI ( p  = ns). Significant factors influencing OS and PFS were > CP1 versus CP1 and Karnofsky performance (KPS) score > 80 versus ≤80, highlighting CP1 patients undergoing allo‐HCT have improved survival compared to >CP1 and the importance of careful allo‐HCT candidate selection.